Phospholipase C‐zeta levels are not correlated with fertilisation rates in infertile couples. (15th October 2021) - Aras‐Tosun, Duru; Cakar, Zeynep; Can, Alp; Ozkavukcu, Sinan; Kaplanoglu, Iskender; Cinar, Ozgur
Abstract: In mammals, 'oocyte activation' is triggered by certain proteins, one of which is phospholipase C‐zeta. Recent evidence suggests that low expression of phospholipase C‐zeta might be associated with male infertility, while a limited number of studies claimed the opposite. This study was designed to test whether quantity of phospholipase C‐zeta and in vitro fertilisation rates are correlated or not, assessed by flow cytometry. Semen samples from 43 infertile couples were analysed for the percentage and mean fluorescent intensity (MFI) of phospholipase C‐zeta protein. Results were confirmed by immunofluorescent labelling. Patients with a fertilisation rate of 40% or lower were involved in the low fertilisation group, while the high fertilization group consisted of patients with a fertilisation rate of 60% and higher. Quantitative analyses by flow cytometry showed no significant difference among the low fertilisation and high fertilisation groups when phospholipase C‐zeta ratio or MFI was considered. No correlation was found between pregnancy rates and phospholipase C‐zeta quantity. None of the total fertilisation failure cases were lack of phospholipase C‐zeta. In fact, fertilisation was possible even when phospholipase C‐zeta levels were very low. Thus, we concluded that phospholipase C‐zeta quantity cannot be considered as a diagnostic tool for male infertility.